Caesalpinioideae (leguminosae) lenhosas na Estação Ambiental de Volta Grande, Minas Gerais, Brasil Woody Caesalpinioideae (leguminosae) species at the Estação Ambiental de Volta Grande, Minas Gerais, Brazil - Fabiana Luiza Ranzato Filardi; Flávia Cristiana Pinto Garcia; Rita Maria de Carvalho Okano (Revista Árvore, 2009)
Este trabalho apresenta o levantamento florístico das Caesalpinioideae lenhosas nas formações de Cerrado e de Floresta Semidecidual, da Estação Ambiental de Volta Grande. A área de estudo, localizada no Triângulo Mineiro, faz parte do complexo da Usina Hidrelétrica Estadual de Volta Grande, reúne 391 ha e retrata 30 anos de regeneração natural. Foram registrados 14 táxons da subfamília, reunidos em 11 gêneros e quatro tribos. Caesalpinieae foi a tribo mais representada (Dimorphandra Schott, Diptychandra Tul, Peltophorum (Vogel) Benth., Pterogyne Tul. e Tachigali Aubl.), seguida por Cassieae (Apuleia Mart., Chamaecrista Moench e Senna Mill.), Detarieae (Copaifera L. e Hymenaea L.) e Cercideae (Bauhinia L.). O gênero mais representativo foi Senna (4 spp.), enquanto os demais foram representados por uma espécie cada. Apresentam-se chave para identificação, descrições e ilustrações, além de comentários sobre a distribuição geográfica dos táxons encontrados. This work presents the floristic survey of woody Caesalpinioideae taxa in the "Cerrado" and Semideciduous Forest vegetation, at the Estação Ambiental de Volta Grande. The area of study is located in the Triângulo Mineiro and belongs to the Companhia Energética de Minas Gerais. It covers 391 ha and represents 30 years of natural regeneration. Fourteen taxa were reported for the subfamily, distributed in 11 genera and four tribes. Caesalpinieae was the most representative tribe (Dimorphandra Schott, Diptychandra Tul., Peltophorum (Vogel) Benth., Pterogyne Tul. and Tachigali Aubl.), followed by Cassieae (Apuleia Mart., Chamaecrista Moench and Senna Mill.), Detarieae (Copaifera L. and Hymenaea L.) and Cercideae (Bauhinia L.). The most representative genus was Senna (4 spp.). Each one of the others was represented by one species. Identification key, descriptions and illustrations are presented for the sampled taxa, besides comments about their geographical distribution.